Determinants of financial Inclusion in Zambia - Makoetje, Reatile Nthati (My University, 2018)
Financial inclusion is a major issue in Zambia, understanding what determines financial inclusion in this country is crucial as it plays a huge role in boosting economic activity and economic growth. Due to multiple uncertainties in the economic environment, it is of great importance to have an appropriate understanding of the factors that have been instrumental in the great improvement in the financial inclusion metrics in Zambia over the years. This study seeks to establish the main determinants of financial inclusion in Zambia. We use the FinScope Household Survey data (2009 and 2015) that covers several household characteristics to perform Probit estimations. Our findings show that residing in the urban areas of Zambia, being a man, older, unmarried, educated (secondary or tertiary) and receiving a consistent income (wage/salaried or self-paid) significantly encourages financial inclusion, with a higher effect on education and income. We observe that formal financial services and informal financial services are the main drivers of financial inclusion in Zambia, still, with education and income having a greater effect in explaining the use of these services, leading to increased financial inclusion in Zambia. Our findings show that polices aimed at including those residing in rural areas and the uneducated are needed to better include this population, policies aimed at the inclusion of women in the country would help in decreasing the gender gap and extending the financial system to rural areas, and technological enhancements will aid in serving the rural population.
Research assignment submitted in fulfilment of the requirements of the degree of Master of Management in Finance and Investment, October 2018
Keywords: Financial institutions--Zambia; Microfinance--Zambia